The City and the University: One Destiny for Two - R. M. Petruneva; V. D. Vasilyeva; B. A. Navrotskiy; Ju. V. Petruneva (Высшее образование в России)
The article is devoted to faculty staff and students of the Stalingrad mechanical Institute who were the participants of the Great Patriotic war and home front workers, considers the destiny of the city and the University as one for two. The authors describe the activities of scientists, teachers and students of the Stalingrad Mechanical Institute during the Great Patriotic War, both during the Battle of Stalingrad and in evacuation in Chelyabinsk. The subject of scientific and applied work devoted to solving a number of technical problems on the creation, improvement and repair of military equipment, mainly the most massive tank of the Great Patriotic War T-34, rocket launchers «Katyusha» and several others. The results of a sociological survey of Volgograd students about their attitude to the Battle of Stalingrad are given. More than 70% of respondents are aware of the names of the heroes of the Battle of Stalingrad, the historic places, streets, squares associated with this event. The young generation carries the historic memory conveyed by the elder generation. The authors believe that it is necessary to develop the historical memory in University students using historic materials, mass media, Internet-resources, family archives, museum expositions.